Implementasi Blockchain Menggunakan Multi-Signature Approval dan Merkle Tree untuk Sistem E-Voting Pemilu - Villeneuve Andhira; Yudi Wibisono; Rizky Rahman (Jurnal Komputer Teknologi Informasi Sistem Komputer (JUKTISI), 2026)
The implementation of conventional general elections in Indonesia still faces significant challenges, including high logistical costs, risks of data manipulation, and a lack of process transparency, which triggers public distrust. This research aims to design a future e-voting system prototype by proposing a Hybrid Voting Framework based on Ethereum blockchain technology and the InterPlanetary File System (IPFS). Scalability and privacy issues are addressed through the integration of the Merkle Tree data structure, where only a 32-byte root value is stored on-chain, while sensitive data is managed off-chain. To mitigate the risk of authority centralization, the system implements a concept from Proof of Authority (PoA) consensus mechanism with a multi-signature approval scheme, requiring the consensus of the majority of validators (>50%) for every administrative action. The test results show that the system is capable of maintaining voting integrity through the one-person-one-vote principle with a stable block creation time of under 10 seconds. Furthermore, the Recent Activity Log and "Verify My Vote" features successfully provide real-time transparency by utilizing event logs from smart contracts. Overall, this prototype proves that the use of blockchain can create a secure, accountable, and efficient voting system, while simultaneously providing maximum privacy protection for voters through robust cryptographic proof.